Vi antigen expression in Salmonella enterica serovar Typhi clinical isolates from Pakistan. - Wain, J; House, D; Zafar, A; Baker, S; Nair, S; Kidgell, C; Bhutta, Z; Dougan, G; Hasan, R (2005)
The accurate identification of Salmonella enterica subsp. enterica serovar Typhi variants that fail to express the capsular polysaccharide, Vi, is an important and much discussed issue for medical microbiology. We have tested a multiplex PCR method which shows the presence or absence of the genetic locus required for Vi expression. Of 2,222 Salmonella serovar Typhi clinical isolates collected from patients' blood over a 4-year period in a region of Pakistan where typhoid is endemic, 12 tested negative for Vi expression by serological agglutination. However, only 1 of these 12 was Vi negative by the multiplex PCR method. This result was confirmed by immunofluorescence, the most sensitive method for Vi characterization in Salmonella serovar Typhi. The multiplex PCR described therefore represents a simple and accurate method for surveillance for Vi-negative variants of Salmonella serovar Typhi in Pakistan. Testing of clinical isolates of Salmonella serovar Typhi, before subculture, from other regions where Vi-negative Salmonella serovar Typhi has been described should be carried out so that the impact of vaccination with purified Vi antigen on the levels of Vi-negative Salmonella serovar Typhi in bacterial populations can be assessed.